Security Aspects of Cloud Based Environments - Suganthi, E; Selvi, F. Kurus Malai (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing is a specialized form of distributed computing. It involves introduction of utilisation models for effective utilisation, remote provisioning, and scalability of measured resources available, ending up in creating useful working environments. Virtualization separates functions from hardware and allows creation of multiple simulated environments or dedicated resources from one physical hardware system to other. It gives specific users, access to packaged resources in ondemand basis, for specific purposes. Virtualisation allows all types of resources to be added to a system, which is managed by a single operating system or Administrator. The concept of virtualization has two serious battles ahead, one is that of data security and the other one is to meet the demand from corporate to store their client data safely. The threat of data breach is generating newer techniques in virtualisation leading to multiple virtual environments being linked,so that it reduces possibility of hardware failure and data security breach. Virtualisation management is also one key element of the virtualisation process and it provides the ability to create, modify, transform and link the virtualised environments in order to effectively manage the environment. With the advent of linking virtual environments, new concept of Multi cloud has come up, wherein multiple cloud services are interconnected or multiple cloud services are accessed by the user for one particular job. This paper proposes to look upon the techniques that shall transform the future of cloud and the security or insecurity that shall come with it